Production of textured ribbons based on Ni–W paramagnetic alloys - Finkel, V.A.; Derevyanko, V.V.; Sungurov, M.S.; Sukhareva, T.V.; Shakhov, Yu.N. (Functional Materials, 2013)
The objective of the work is searching for ways to produce substrates for second generation HTSC-covered conductors based on high tungsten content Ni–W paramagnetic alloys having a cubic texture of {001}< 100> type. The work is based on the following hypothesis: increasing the stacking fault energy Esf, and, as a consequence, cubic structure formation is possible due to rather strong compressive stress in the ribbon. On the conceptions developed, two new ways for production of a cubic texture in the ribbon were realized: (i) TiN thin layer plasma deposition, and (ii) Ni–W alloy rolling under conditions providing dislocation high density ("extreme rolling"). Optimal schemes for mechanical and thermal treatment of paramagnetic Ni–9.5 at. % W alloy based ribbons were developed including choice of synthesis method, rolling regimes parameters, ribbon thickness, annealing temperature and time, etc.